The Impact of Digital Storytelling on Developing Intercultural Communicative Competence in ESL Learners - Tursunkhojyeva, Mokhigul (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This paper explores the role of digital storytelling in enhancing intercultural communicative competence (ICC) among English as a Second Language (ESL) learners. ICC involves the ability to communicate effectively and appropriately across cultural boundaries, integrating linguistic, pragmatic, and sociocultural skills. Traditional ESL instruction often emphasizes grammar and vocabulary but neglects intercultural dimensions. Digital storytelling, which combines narrative construction with multimedia tools, offers learners opportunities to reflect on cultural identity, share experiences, and engage in authentic communication. Findings from recent studies suggest that digital storytelling significantly improves learners’ pragmatic awareness, intercultural sensitivity, and confidence. The paper argues for integrating digital storytelling into ESL curricula to prepare learners for authentic communication in diverse global contexts.